2007
DOI: 10.1016/j.expneurol.2007.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Transduced Schwann cells promote axon growth and myelination after spinal cord injury

Abstract: We sought to directly compare growth and myelination of local and supraspinal axons by implanting into the injured spinal cord Schwann cells (SCs) transduced ex vivo with adenoviral (AdV) or lentiviral (LV) vectors encoding a bifunctional neurotrophin molecule (D15A). D15A mimics actions of both neurotrophin-3 and brain-derived neurotrophic factor. Transduced SCs were injected into the injury center 1 week after a moderate thoracic (T8) adult rat spinal cord contusion. D15A expression and bioactivity in vitro;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 67 publications
7
110
0
Order By: Relevance
“…Indeed, SCs have been shown to promote axonal regeneration and remyelinate regrowing axons in various experimental paradigms of CNS and PNS injury [3,[25][26][27]. These studies support the idea that in humans, after nerve injury, autologous SCs could be obtained from healthy nerves, expanded ex vivo, and retransplanted at the sites of injury [28,29].…”
mentioning
confidence: 74%
“…Indeed, SCs have been shown to promote axonal regeneration and remyelinate regrowing axons in various experimental paradigms of CNS and PNS injury [3,[25][26][27]. These studies support the idea that in humans, after nerve injury, autologous SCs could be obtained from healthy nerves, expanded ex vivo, and retransplanted at the sites of injury [28,29].…”
mentioning
confidence: 74%
“…Additionally, some studies using genetically modified Schwann cells to overexpress the NT-3 gene have examined the role of NT-3 in the neuron survival and axonal regeneration/remyelination (Zhang, Zeng et al 2007;Pettingill, Minter et al 2008). It has been reported that Schwann cells transduced ex vivo with adenoviral (AdV) or lentiviral www.intechopen.com (LV) vectors encoding a functional NT-3 molecule led to the presence of a significantly increased number of axons in the contusion site (Golden, Pearse et al 2007). The results of Yamauchi (Yamauchi, Miyamoto et al 2005) et al showed that NT-3 activation of TrkC stimulates Schwann cell migration through two parallel signaling units, Ras/Tiam1/Rac1 and Dbs/Cdc.…”
Section: Lipus Stimulation Induced An Alteration In Schwann Cell Funcmentioning
confidence: 99%
“…Here, we will discuss some basic technical aspects of using a PNG to promote regeneration, the application of PNGs to a variety of injury conditions (including a delayed grafting [chronic injury] approach), the use of PNGs in a combinatorial treatment strategy, and the translation of peripheral nerve (PN) grafting to large animal models of spinal cord injury (SCI). This review focuses on results obtained from grafting peripheral nerve segments into the injured spinal cord, but it would be remiss not to mention that alternative approaches using components of peripheral nerves (e.g., purified Schwann cells in implantable guidance channels [11][12][13][14][15][16][17][18][19][20][21], or the re-routing of a peripheral nerve from its target muscle to enter the spinal cord distal to an injury [22][23][24]) have demonstrated considerable success in establishing connectivity across a lesion site. Notably, the number of Electronic supplementary material The online version of this article (doi:10.1007/s13311-011-0024-6) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%